PENDEKATAN METODE MAUT PADA FITUR SELEKSI DALAM SISTEM INFORMASI ADMINISTRASI BERBASIS WEB KWARTIR RANTING BATANG KUIS - Suci Syah Putri; Suendri (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
The administration and coaching systems in the Batang Kuis Scout Branch are still carried out manually, including data recording, correspondence management, and participant selection processes. This leads to workflow delays, increased risk of data recording errors, and low accuracy in decision-making. These issues significantly affect organizational efficiency and fairness in participant selection. This study aims to develop a web-based information system integrated with the Multi-Attribute Utility Theory (MAUT) method as a decision support feature to ensure objective, transparent, and efficient participant selection. A quantitative research approach was applied, direct user testing to evaluate system effectiveness. The developed system includes features for managing scoutmasters, Scout Units (Gudep), correspondence (incoming and outgoing letters), activity documentation, and a MAUT-based selection module that processes five main criteria: Administration, Scout Knowledge, National Insight, Personal Characteristics, and Marching Ability (LKBB). Selection data was collected through observation and participant score documents, then processed using the MAUT method to generate accurate participant rankings. The results show that the system achieved 92.5% selection accuracy and improved selection efficiency by up to 78% compared to conventional methods. In conclusion, the system successfully improves the effectiveness and accuracy of the selection process while strengthening organizational administrative governance. The implication of this research is that the system can serve as an integrated digital solution, which can be adopted by other scout branches as a foundational step toward digital transformation in scouting organizational management, ensuring sustainability and transparency.